2019
DOI: 10.1136/archdischild-2018-316066
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury in young children with isolated scalp haematoma

Abstract: ObjectiveDespite high-quality paediatric head trauma clinical prediction rules, the management of otherwise asymptomatic young children with scalp haematomas (SH) can be difficult. We determined the risk of intracranial injury when SH is the only predictor variable using definitions from the Pediatric Emergency Care Applied Research Network (PECARN) and Children’s Head Injury Algorithm for the Prediction of Important Clinical Events (CHALICE) head trauma rules.DesignPlanned secondary analysis of a multicentre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Of the three children <2 years with ciTBI in the intermediate‐risk category, two had an isolated non–frontal scalp hematoma and one had both a scalp hematoma and did not act normally according to parents. Previous secondary analyses of the PECARN and APHIRST original data set have provided detailed risk estimates of ciTBI for each intermediate‐risk predictor in isolation (meaning no other signs or symptoms of ciTBI), namely, vomiting, loss of consciousness, scalp hematoma, severe mechanism of injury, severe headache, and child not acting normally as per guardian; in isolation they were associated with a very low risk of ciTBI of less than 1% 16,19–25 . Our study adds to this literature by providing ciTBI risk estimates for different combinations of predictors within the PECARN high‐ and intermediate‐risk groups.…”
Section: Discussionmentioning
confidence: 82%
“…Of the three children <2 years with ciTBI in the intermediate‐risk category, two had an isolated non–frontal scalp hematoma and one had both a scalp hematoma and did not act normally according to parents. Previous secondary analyses of the PECARN and APHIRST original data set have provided detailed risk estimates of ciTBI for each intermediate‐risk predictor in isolation (meaning no other signs or symptoms of ciTBI), namely, vomiting, loss of consciousness, scalp hematoma, severe mechanism of injury, severe headache, and child not acting normally as per guardian; in isolation they were associated with a very low risk of ciTBI of less than 1% 16,19–25 . Our study adds to this literature by providing ciTBI risk estimates for different combinations of predictors within the PECARN high‐ and intermediate‐risk groups.…”
Section: Discussionmentioning
confidence: 82%
“…6 A more recent study compared PECARN and CHA-LICE prediction rules for risk of ciTBI/TBI in infants with ISH using a large prospective cohort of head-injured children enrolled in EDs located in Australia and New Zealand. 11 Using the PECARN rule the risk of ciTBI in infants younger than 1 year with ISH was 0% (95% CI = 0.3% to 3.3%), compared with 20% (95% CI = 8.4% to 36.9) using the CHALICE prediction rule. However, for the PECARN analysis the numbers were low (109 infants) and 12.5% had TBI on CT. Additionally, only overall risk for ciTBI and TBI on CT were reported without more granular analysis of specific predictors.…”
Section: Discussionmentioning
confidence: 93%
“…In a secondary analysis of the PECARN TBI study of children < 2 years of age with an ISH, younger age, nonfrontal location and larger hematoma size location as well as mechanism of injury were each associated with higher risk of TBI; however, each predictor in isolation gives limited guidance regarding an individual infant’s specific risk 6 . A more recent study compared PECARN and CHALICE prediction rules for risk of ciTBI/TBI in infants with ISH using a large prospective cohort of head‐injured children enrolled in EDs located in Australia and New Zealand 11 . Using the PECARN rule the risk of ciTBI in infants younger than 1 year with ISH was 0% (95% CI = 0.3% to 3.3%), compared with 20% (95% CI = 8.4% to 36.9) using the CHALICE prediction rule.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,12,13 The degree to which these data apply to infants <3 months old is unclear; however, prior studies suggest that younger infants with isolated small scalp hematomas are at higher risk of traumatic brain injury on CT compared to older infants and children. 6,21,31,32 One study demonstrated that among infants younger than 2 years with isolated scalp hematomas, clinically important traumatic brain injuries occurred in 2.2% of those <3 months old, compared to 0.3% of children between 3 and 24 months old. 6 In conclusion, the PECARN traumatic brain injury lowrisk criteria accurately identified infants younger than 3 months at low risk of clinically important traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%